2022
DOI: 10.20473/mkp.v35i12022.14-27
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roots of local government corruption practices in rural Java: An anthropological analysis

Abstract: Corruption is a crucial issue in Indonesia, including in the administration of village government. This article aims to explain the roots of corruption seen from an anthropological analysis of corruption. This article describes the factors causing corruption practices in rural Java, i.e., local values in village governance practices. The research was conducted in several villages in Bojonegoro Regency-East Java. The data were collected through a series of participatory observations, in-depth interviews, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The smart village model described in their research includes six smart city missions, one of which focuses on transparency, particularly financial transparency. Given that village governments often face challenges in financial administration, the urgent need for technology to improve the administration process and provide a software system is evident [63,70,71].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The smart village model described in their research includes six smart city missions, one of which focuses on transparency, particularly financial transparency. Given that village governments often face challenges in financial administration, the urgent need for technology to improve the administration process and provide a software system is evident [63,70,71].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Previous research in Sumorame Village, Candi District, and Sidoarjo Regency showed that the community still did not realize the importance of transparency for public welfare, and transparency by the Village Government only served to achieve specific formality goals based on implementing applicable regulations (Ardelia & Handayani, 2022). A previous study entitled "Exploring the roots of local government corruption practices in rural Java: An anthropological analysis" provides clues that deviations related to village financial management are caused by non-value factors such as the loyalty of the followers of the Village Head, vital harmony, and the ability of the Village Head to manifest himself as an ideal leader (Setiadi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%